The Violence of Modernity Baudelaire, Irony, and the Politics of Form - Sanyal, Debarati (Johns Hopkins University Press, 2006)
The Violence of Modernity turns to Charles Baudelaire, one of the most canonical figures of literary modernism, in order to reclaim an aesthetic legacy for ethical inquiry and historical critique. Works of modern literature are commonly theorized as symptomatic responses to the trauma of history. In a climate that tends to privilege crisis over critique, Debarati Sanyal argues that it is urgent to rethink literary experience in terms that recall its contestatory potential. Examining Baudelaire's poems afresh, she shifts the focus of critical attention toward an account of modernism as an active engagement with violence, specifically the violence of history in nineteenth-century France.Sanyal analyzes a literary current that uses the traditional hallmarks of modernism-irony, intertextuality, self-reflexivity, and formalism-to challenge the historical violence of modernity. Baudelaire and the committed ironists writing in his wake teach us how to read and resist the violence of history, and thereby to challenge the melancholy tenor of our contemporary "wound culture." In a series of provocative readings, Sanyal presents Baudelaire's poetry as an aesthetic form that contests historical violence through rhetorical strategies of complicity, counterviolence, and critique. The book develops a new account of Baudelaire's significance as a modernist by dislodging him both from his traditional status as a practitioner of "art for art's sake" and from his more recent incarnation as the poet of trauma. Following her extended analysis of Baudelaire's poetry, Sanyal in later chapters considers a number of authors influenced by his strategies-including Rachilde, Virginie Despentes, Albert Camus, and Jean-Paul Sartre-to examine the relevance of their interventions for our current climate of trauma and terror. The result is a study that underscores how Baudelaire's legacy continues to energize literary engagements with the violence of modernity.